2012
DOI: 10.1186/1471-2253-12-22
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical effect of hyperventilation on speed of recovery and risk of rehypnotization following recovery - a GasMan®simulation

Abstract: BackgroundHyperventilation may be used to hasten recovery from general anesthesia with potent inhaled anesthetics. However, its effect may be less pronounced with the newer, less soluble agents, and it may result in rehypnotization if subsequent hypoventilation occurs because more residual anesthetic will be available in the body for redistribution to the central nervous system. We used GasMan® simulations to examine these issues.MethodsOne MAC of isoflurane, sevoflurane, or desflurane was administered to a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…To study uptake, distribution and elimination of inhalational anesthetics, the Gas Man simulation software has been used extensively [24][25][26][27][28]. This research report is based on simulation data and does not involve human subjects, either directly or indirectly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study uptake, distribution and elimination of inhalational anesthetics, the Gas Man simulation software has been used extensively [24][25][26][27][28]. This research report is based on simulation data and does not involve human subjects, either directly or indirectly.…”
Section: Methodsmentioning
confidence: 99%
“…The theoretical model is able to reproduce the kinetic relationships described by Kety and explored by Eger [ 12 , 26 , 31 , 32 ]. Furthermore, the Gas Man simulation model has been used extensively in pharmacokinetic studies to investigate the uptake, distribution and elimination of volatile anesthetics during different clinical settings [ 25 , 27 , 33 , 34 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…3) and therefore less slowing of tissue washout kinetics (equation 9 for τ late ). It has been taught intuitively for many years that lower blood gas solubility leads to faster overall uptake and elimination kinetics, 1-3,6,9-11,13,24 a fact completely consistent with experimental data, 6,14-20,23,24 mathematical models of kinetics solved numerically 2,5,[9][10][11]13,23,24,34 or analytically, 4,28 and routine clinical experience. Surprisingly, however, it is hard to find in previous literature any equation that directly shows a connection between the overall terminal elimination time constant and blood gas solubility.…”
Section: Discussionmentioning
confidence: 85%
“…This equation for fractional clearance has been presented previously. 1,2,34,46 Retention and fractional clearance curves for a desflurane blood/gas partition coefficient in pig blood of 0.40 43 are shown in figure 3, with three points on each curve corresponding to our experimental values of . V A / .…”
Section: Perioperative Medicinementioning
confidence: 99%
“…De Wolf and colleagues 16 demonstrated that hyperventilation to achieve rapid emergence from anaesthesia does not greatly speed waking up from insoluble agents and does not result in re-anaesthetization unless hypoventilation is severe or unless a highly soluble agent (e.g. isoflurane) is used.…”
Section: Improving Clinical Carementioning
confidence: 99%